2004
DOI: 10.1038/sj.bjp.0705682
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microglial inflammatory response by sodium butyrate and short‐chain fatty acids

Abstract: 1 Recent studies have shown that sodium butyrate and other short-chain fatty acids (SCFAs) can prevent inflammation in colon diseases. Our aim was to elucidate whether sodium butyrate and SCFAs regulate the inflammatory responses in different neural inflammation models in cell cultures. 2 Inflammatory responses to LPS-induced microglial activation were recorded by the secretion of nitric oxide (NO) and cytokines IL-6 and TNF-a and related to the changes in the DNA-binding activities of NF-kB complex. 3 We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(166 citation statements)
references
References 26 publications
10
147
2
1
Order By: Relevance
“…1C) and so it makes sense that it can serve as a control point for limiting the IR (Suuronen et al, 2003). Indeed, several studies have reported a decrease in the TLR4/NF-κB response to LPS following butyrate administration (Huuskonen et al, 2004;Wu et al, 2012). In addition to reductions in NF-κB family genes, we propose that butyrate limits the extent of the immune response to LPS by reducing the expression of additional genes shown to be effectors of the IR.…”
Section: Gene Expression and Pathway Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…1C) and so it makes sense that it can serve as a control point for limiting the IR (Suuronen et al, 2003). Indeed, several studies have reported a decrease in the TLR4/NF-κB response to LPS following butyrate administration (Huuskonen et al, 2004;Wu et al, 2012). In addition to reductions in NF-κB family genes, we propose that butyrate limits the extent of the immune response to LPS by reducing the expression of additional genes shown to be effectors of the IR.…”
Section: Gene Expression and Pathway Analysismentioning
confidence: 79%
“…Here we report that butyrate supplementation increases plasma levels of LBP. However, this effect may be muted by the addition of butyrate, as several groups have reported reductions in the downstream effects of LPS-mediated induction of the immune system (Chakravortty et al, 2000;Huuskonen et al, 2004;Morikawa et al, 2004;Ni et al, 2010) under similar conditions. In addition, SAA, also an acute phase protein, was unaffected by the addition of butyrate.…”
Section: Physiological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellularly, ischemic damage results in an increased transcription rate of genes that control cellular stress, inflammatory, and apoptotic response genes. Interestingly, several groups have reported that treatment with various HDACis, SAHA, SB, and TSA, both prior to and following stroke induction, confers neuroprotection (82,115,142,161,162,277,282,316). The idea that HDACis might be neuroprotective against ischemic cell damage originates in the observation that following cerebral artery occlusion, an animal model to induce ischemia, H3 acetylation levels show a pronounced decrease (82).…”
Section: B Stroke/ischemiamentioning
confidence: 99%
“…In mouse cells, sodium butyrate also inhibits hypoxia-induced iNOS protein and down-regulation of TNF-α messenger RNA, thus reducing the inflammatory response [143]. Sodium butyrate can also induce an adaptive response to LPS-stimulated microglial activation by attenuating NO, IL-6, and TNF secretion-all classic microglial inflammatory responses [144]. However, this anti-inflammatory activity may be specific to short-chain fatty acid HDACi, as the hydroxamate HDACi, TSA and SAHA, strongly potentiate the LPS-induced inflammatory response in primary microglial, neural co-cultures, and hippocampal slices [145].…”
Section: Hdaci and Astrocytesmentioning
confidence: 99%